Inovasi Pembelajaran: Penerapan Kuis Interaktif dalam Pembelajaran Kosakata Bahasa Arab - Amal, Islakhul; Anwar, Najih (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Among the many media that can be used in direct or indirect learning, one of them is interactive quizzes. Interactive quizzes themselves are media or applications that contain learning materials in the form of interactive questions that make students able to increase their insight and knowledge about learning materials and can be developed as an alternative to independent learning. The purpose of this study is to find out how the responses obtained by the students from learning using the interactive tools they get. This study uses a descriptive quantitative method, namely research that presents the data in the form of numbers which are then described to complement the description. This research will be conducted on 32 students of class X-3 at SMA Muhammadiyah 3 Tulangan as a sample. The data collection technique will be carried out using a questionnaire that will be distributed to students containing questions to find out the students' responses to the implementation of Arabic vocabulary learning using interactive quizzes on the classpoint application. The questionnaire will be given to each student in the form of a sheet of paper whose statement has been validated by an expert. This study resulted in a conclusion that the use of Interactive Quizzes in Learning Arabic Vocabulary in the ClassPoint application received a positive response from students in class X-3 of SMA Muhammadiyah 3 Tulangan. The positive response given by the students after carrying out the research can be a determinant of how the students' learning development will be next.